2018
DOI: 10.1111/ejss.12717
|View full text |Cite
|
Sign up to set email alerts
|

Soil aeration: the relation between air‐filled pore volume and redox potential

Abstract: Summary The soil water content affects rates of oxygen diffusion and redox potentials (EH). When water‐saturated soils become aerated, a switch from reducing to oxidizing conditions occurs. However, limited information is available on the air‐filled pore volume (ϵ) at which this shift happens. To obtain values of ϵ, undisturbed soil cores were taken from a Fluvisol and a Gleysol that differed in structure and clay content. Experiments on submergence and drying following a new experimental design were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
(38 reference statements)
3
18
0
Order By: Relevance
“…) reflects small‐scale variations in soil aeration and redox status and is well in agreement with the findings by Dorau et al. (). They demonstrated small scale variations in re‐oxidation (increasing E H ) of microsites and a close linkage between E H and air‐filled pore volume (ε) in structured soil cylinders during air drying of the previously submerged soil samples.…”
Section: Discussionsupporting
confidence: 92%
“…) reflects small‐scale variations in soil aeration and redox status and is well in agreement with the findings by Dorau et al. (). They demonstrated small scale variations in re‐oxidation (increasing E H ) of microsites and a close linkage between E H and air‐filled pore volume (ε) in structured soil cylinders during air drying of the previously submerged soil samples.…”
Section: Discussionsupporting
confidence: 92%
“…+ and NO 3 − along the soil profile varied in response to irrigation and fertilization (Figure 9b,c), similar to the study of Rubol et al [16]. Before fertilization, the soil Eh was low in the lower parts of the soil column (Figure 2b), since during the prolonged soil saturation the active soil microorganisms use alternative electron acceptors instead of oxygen [52][53][54]. Therefore, consistent with the high consumption rate of nitrate at −11 cm (Figure 9a), the Eh decreased even further and faster at −11 cm (Figure 2b).…”
Section: Effects Of Soil Hydrological Conditions On Eh and Dissolved Nsupporting
confidence: 84%
“…Multiple water retention curves of soil samples from the same study site and the same depth have been obtained in a previous study. A detailed description can be found in Dorau et al (2018), which is also the conceptual and experimental basis for this study in conjunction with μCT 3D-image-analysis. We used the evaporation method with an HYPROP device (UMS, Munich, Germany) that measures a decrease in matric potential during evaporation of an initial water-saturated soil sample by two minitensiometers (5 mm Ø).…”
Section: Water Retention Curve and Air-filled Pore Volumementioning
confidence: 99%
“…Recent statistical approaches to quantify biogeochemical heterogeneity derived from a multitude of E H readings are more than welcome (Wanzek et al, 2018). One approach to characterise the aeration status was proposed by Dorau et al (2018), where undisturbed soil samples were equipped in parallel with Pt electrodes to record the E H and micro tensiometers for the soil matric potential and thereupon calculate the air-filled pore space (ε). The authors identified soil-specific ε threshold values that characterise the ecologically important shift from anaerobic to aerobic soil microbial metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation